China’s Laws on Sexual Harassment in Schools: Making Comparison with U.S. Laws - Shan, Zixuan (Transactions on Social Science, Education and Humanities Research, 2025)
In China, The Flaws Lack in the Institutions to Flexible Accessibility for the Higher Education Systems. Using comparative legal analysis and substantive empirical case studies, including court rulings, policy evaluation, and Chinese nationwide surveys of schools, this study explores the difference of China’s ad-hoc response mechanisms and the U.S. Title IX model. Between 2012 and 2021, the lack of clear legal definitions, schools’ reputation preservation and protective policies, and cultures of shame independently revealed three systemic weaknesses across China: ambiguity of laws prohibiting SVA, school policies prioritizing reputation management over victims’ protections, and cultures that stigmatize reporting that lowers reporting rates. The analysis shows that standardized grievance procedures, proportional staffing of investigators, and punitive damages for institutional negligence, could massively enhance accountability in China if implemented within its governance context. Recommendations to address harassment laws are implementing specific laws that would provide clear definitions of harassment for different types of technology used, joint investigative committees led by education bureaus and increased anti-harassment training as part of teacher certification295295704 policy. Importantly, China can use its centralized administrative structure to carry out nationwide school compliance audits while piloting restorative justice programs to address cultural resistance. This study thus concludes that where bridges are necessary for balancing legal hardiness with cultural adaptability, the transplantation of foreign laws in itself is far from sufficient for establishing an enduring paradigm of protection centered on the victim, which can replace the transient, media-motif paradigm of protection for justice-seekers in China.